Steamboat ELDORADO caught in the ice on the Yukon River en route to Dawson from Whitehorse, Yukon Territory, ca. 1901. - University of Washington Libraries. Special Collections Division
PH Coll 246.39 [Meed journal: "Steamer "Eldorado" en route to Dawson from White Horse. When about halfway she was caught by the winter freeze-up and although in a dangerous position, luckily escaped and finished the jouney eight months later in the spring break-up."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number